The Scarcity–Prosociality Link: Ambiguous, Yet Thought-provoking. (March 2022) - Krishnan, Lilavati
The present essay examines the scarcity–prosociality link, that is, the conditions in which scarcity leads to self-interest and competitiveness or to other-oriented prosociality and cooperativeness. Adopting a social-psychological approach, the findings of the major investigations of reactions to scarcity are summarised. These studies show both self-interest and prosociality as reactions to scarcity, depending on various mediating factors, although a scarcity mindset or limited-good perception is not revealed directly. This link needs to be interpreted in the light of social-psychological, cognitive, economic and cultural factors. In general, the scarcity–prosociality relationship is found to be ambiguous, yet thought-provoking. Some aspects that require detailed exploration and the multi-pronged implications of the scarcity–prosociality association for societal development are highlighted. It is suggested that effective coping with scarcity in resource-constrained economies will be possible if socialisation and social policies promote practices that enhance resource availability, encourage an optimal use of resources, and modify a competitive stance to a cooperative one, and a zero-sum game perception of resource exchange to one of non-zero-sum game.